"And Understand I am a Person and Not Just a Number:" Reproductive Healthcare Experiences of Italian Women. Issue 1 (2nd January 2021) - Meier, Stephanie; Carter, Martasia M.; DeMaria, Andrea L.
Abstract: Patient-centered care may provide women autonomy in their reproductive health choices. The study's objective was to explore Italian women's reproductive health decision-making experiences through a shared decision-making lens. Researchers conducted 46 interviews (June-July, 2017) with women ages 18-45 living in or near Florence, Italy. Expanded grounded theory was used to explore women's experiences. Findings suggest the Italian women in this sample desire decision-making involvement but conceptualize this as listening, respect, and information provision. Social network served an important function in decision-making. The economy and religion influenced decision-power. Findings offer practical recommendations to guide patient-centered care opportunities in Italy.